Qualitative characterizations of relationships among South African adolescent girls and young women and male partners: implications for engagement across HIV self‐testing and pre‐exposure prophylaxis prevention cascades. (30th June 2020) - Holmes, Leah E; Kaufman, Michelle R; Casella, Albert; Mudavanhu, Mutsa; Mutunga, Lillian; Polzer, Tara; Bassett, Jean; Van Rie, Annelies; Schwartz, Sheree
Abstract: Introduction: Adolescent girls and young women (AGYW) in sub‐Saharan Africa have emerged as a priority population in need of HIV prevention interventions. Secondary distribution of home‐based HIV self‐test kits by AGYW to male partners (MP) is a novel prevention strategy that complements pre‐exposure prophylaxis (PrEP), a female‐controlled prevention intervention. The objective of this analysis was to qualitatively operationalize two HIV prevention cascades through the lens of relationship dynamics for secondary distribution of HIV self‐tests to MP and PrEP for AGYW. Methods: From April 2018 to December 2018, 2200 HIV‐negative AGYW aged 16‐24 years were enrolled into an HIV prevention intervention which involved secondary distribution of self‐tests to MP and PrEP for AGYW; of these women, 91 participants or MP were sampled for in‐depth interviews based on their degree of completion of the two HIV prevention cascades. A grounded theory approach was used to characterize participants' relationship profiles, which were mapped to participants' engagement with the interventions. Results: In cases where AGYW had a MP with multiple partners, AGYW perceived both interventions as inviting distrust into the relationship and insinuating non‐monogamy. Many chose not to accept either intervention, while others accepted and attempted to deliver the self‐test kit but received a negative reaction from their MP. In the few cases where AGYW held multiple partnerships, both interventions were viewed as mechanisms for protecting one's health, and these AGYW exhibited confidence in accepting and delivering the self‐test kits and initiating PrEP. Women who indicated intimate partner violence experiences chose not to accept either intervention because they feared it would elicit a violent reaction from their MP. For AGYW in relationships described as committed and emotionally open, self‐test kit delivery was completed with ease, but PrEP was viewed as unnecessary. MP experience with the cascade corroborated AGYW perspectives and demonstrated how men can perceive female‐initiated HIV prevention options as beneficial for AGYW and a threat to MP masculinity. Conclusions: Screening to identify AGYW relationship dynamics can support tailoring prevention services to relationship‐driven barriers and facilitators. HIV prevention counseling for AGYW should address relationship goals or partner's influence, and engage with MP around female‐controlled prevention interventions.